INTERTEXTUALITY IN NEWSPAPER DISCOURSE (A COMPARATIVE ANALYSIS OF HYBRID MEDIA CONTEXTS) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
Intertextuality is a key meaning-making mechanism in newspaper discourse, enabling texts to draw on prior cultural, political, and media narratives. With the emergence of digital journalism, the nature of intertextual practices has fundamentally changed, expanding from classical institutional references to multimodal, hyperlinked, and socially generated intertexts. This study conducts a comparative analysis of intertextuality in print and online newspapers within hybrid media contexts. A corpus of 60 articles from The Guardian, The New York Times, Xalq so‘zi (print), and their online counterparts (guardian.com, nytimes.com, xs.uz) was examined. Results show that online newspapers demonstrate higher intertextual density and greater reliance on digital mediatexts (hyperlinks, social-media posts, memes), whereas print newspapers rely predominantly on political, historical, and literary intertexts to establish authority. These findings reveal that hybrid media discourse not only transforms the form and function of intertextuality, but also reshapes journalistic strategies of persuasion, contextualization, and ideological framing.